Analysis of Water Conservation Management and Plumbing Systems at the Stiba Makassar Campus - Ariesman, Ariesman; Musriwan, Musriwan; Herman, Sulkifli; Rosmita, Rosmita; Juniar, Juniar (Journal of Fisheries and Marine Applied Science, 2024)
This research aims to analyze the level of water conservation and the condition of the plumbing system and provide recommendations for increasing water conservation and improving the plumbing system on the STIBA Makassar campus. The research method uses qualitative and quantitative approaches. The results of the research show that the STIBA Makassar campus has demonstrated its commitment to water conservation management through the efforts made which have resulted in several water management efficiencies. From the data that has been obtained, it can be seen that several steps have been taken to managing water well, such as using Waste Water Treatment Plants (IPAL), managing kitchen waste water, maintaining open green land and tree planting movements. The additional use of biopores in front of the Anas bin Malik Mosque also shows awareness of the importance of managing waste water or rain effectively. Meanwhile, the plumbing system shows that the efficiency of the plumbing system that has been implemented in accordance with the SNI 8153:2015 standard shows good steps in maintaining the quality of the plumbing system on campus. It was found that there were 8 elements that had not been fully implemented, such as Backflow Preventing Devices, Traps Under Buildings, Position of Standpipes, and others. Research recommendations include strengthening sustainable awareness education about the importance of water conservation, carrying out management efforts through reusing water that has been used, such as seeping it back into the soil through infiltration wells or building reservoirs. Utilization of rainwater during the rainy season is by filling distribution reservoirs to save on pump electricity usage, while plumbing systems that have not yet been implemented can be implemented in stages and carry out routine maintenance and upkeep, as well as in the procurement of new buildings, you need to pay attention to the plumbing system according to standards.